2021
DOI: 10.21203/rs.3.rs-157719/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Computed Tomography-assisted Limited Decompression in the Surgical Management of Thoracolumbar Fractures With Neurological Deficit

Abstract: Objective: to investigate the effect of CT-assisted limited decompression in the management of single segment A3 lumbar burst fracture. Method: A retrospective study of 106 cases with a single-level Magerl type A3 lumbar burst fractures treated with short-segment posterior internal fixation and limited decompression from January 2015 to June 2019 was performed. Patients were divided into two groups: CT-assisted and non-CT-assisted. Perioperative factors, clinical outcomes, postoperative complications, imaging … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The effect of hypoxia on different subtypes is inherently heterogeneous. Nakamura et al found that pretreatment anemia was not associated with the prognosis of liposarcoma, while malignant fibrous histiocytoma was the opposite [23,42] . Patients may differ from study to study, so heterogeneity is acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of hypoxia on different subtypes is inherently heterogeneous. Nakamura et al found that pretreatment anemia was not associated with the prognosis of liposarcoma, while malignant fibrous histiocytoma was the opposite [23,42] . Patients may differ from study to study, so heterogeneity is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al found that pretreatment anemia was not associated with the prognosis of liposarcoma, while malignant fibrous histiocytoma was the opposite. [23,42] Patients may differ from study to study, so heterogeneity is acceptable. Second, the cutoff values between different studies are different.…”
Section: Survival Analysismentioning
confidence: 99%